1979
DOI: 10.1111/j.1471-0528.1979.tb10714.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Polyamine Oxidase Activity in the Fetomaternal Compartments

Abstract: Summary Polyamine oxidase activity was measured in different compartments of the feto‐maternal unit by a radiochemical method. The activity in the retroplacental serum (mainly of intervillous origin) was 20 to 30 times higher than in maternal uterine or peripheral venous blood sera. No activity was found in the fetal cord blood sera. The enzyme level in the maternal peripheral sera fell to undetectable levels within 72 hours post partum. Preliminary data indicate that the enzyme might be produced by the decidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Whether indeed we are dealing with a single enzyme protein with broad substrate specificity or a family of enzymes is for the most part not known with certainty (see Morgan, 1983). Amine oxidase activity has been detected as DAO with putrescine as substrate (Gahl et al, 1982a;Southren et al, 1964), polyamine oxidase (PAO) with spermine as substrate (Dlei and Morgan, 1979), histaminase with histamine as substrate (Beavan et al, 1975) and spermidine oxidase with spermine as substrate (Gahl et al, 1982a). Amine oxidase has been purified and characterized from a number of sources including maternal serum (Illei and Morgan, 1979;Gahl et al, 1982a), maternal plasma (Baylin and Margolis, 1975), amniotic fluid (Tujvesson, 1978), and term placental tissue (Smith, 1967;Paolucci«ai., 1971;Bardsley etal., 1974;Crabbe etal., 1976) (see Morgan, 1983).…”
Section: Scbeumentioning
confidence: 97%
“…Whether indeed we are dealing with a single enzyme protein with broad substrate specificity or a family of enzymes is for the most part not known with certainty (see Morgan, 1983). Amine oxidase activity has been detected as DAO with putrescine as substrate (Gahl et al, 1982a;Southren et al, 1964), polyamine oxidase (PAO) with spermine as substrate (Dlei and Morgan, 1979), histaminase with histamine as substrate (Beavan et al, 1975) and spermidine oxidase with spermine as substrate (Gahl et al, 1982a). Amine oxidase has been purified and characterized from a number of sources including maternal serum (Illei and Morgan, 1979;Gahl et al, 1982a), maternal plasma (Baylin and Margolis, 1975), amniotic fluid (Tujvesson, 1978), and term placental tissue (Smith, 1967;Paolucci«ai., 1971;Bardsley etal., 1974;Crabbe etal., 1976) (see Morgan, 1983).…”
Section: Scbeumentioning
confidence: 97%
“…Spermine oxidase (SMOX), an enzyme that preferentially oxidizes spermine, a polyamine involved in cellular metabolism and suggested to play a role in immune privilege in the decidua [32], increased 17.4-fold in cAMP-treated MSC compared to cells treated with vehicle for 14 days. It was also 5.8-fold up-regulated in hESF in response to cAMP (Table 1) [23].…”
Section: Comparison Of Response To 8-br-camp In Msc Versus Hesfmentioning
confidence: 99%
“…We have previously suggested that the enzyme in sufficient concentrations may constitute an important part of a supposed local immunological barrier formed at the placental bed to protect the fetal allograft from maternal immune rejection through a local suppressive effect on maternal cellular immunity. The P A 0 activity found in the maternal circulation might be the consequence of a leakage, rather than secretion, into the maternal blood (Illei and Morgan, 19796) and might not be high enough to cause a generalized suppression of the maternal cellular immunity. We have also shown that the enzyme activity of decidua is significantly higher than that of placenta.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that in the retroplacental serum (mainly of intervillous origin) the P A 0 activity is 20 to 30 times higher than in the maternal uterine or cubital venous blood serum. No activity was found in fetal cord blood serum and preliminary data indicate that the enzyme might be produced by the decidua rather than by the placenta (Illei and Morgan, 19796). Recent only in retroplacental serum, is able to inhibit the spontaneous proliferation of lymphocytes in vitro (Morgan and Illei, 1980a).…”
mentioning
confidence: 99%